Systematic Literature Review: Factors Affecting The Quality Of Local Government Financial Reports In Indonesia - Nurul Huda; Enggar Diah Puspa Arum; Wira Lestari (International Journal of Economics, Business and Innovation Research, 2025)
Research Objectives : This research uses a bibliometric Systematic Literature Review (SLR) which aims to determine the factors that influence the quality of regional government financial reports in Indonesia and then map these studies. Method/Approach : This research is a bibliometric-based Systematic Literature Review (SLR) related to factors that influence the quality of local government financial reports in Indonesia and then mapping these studies. Results : This study shows that it can be useful for local governments in making decisions to realize effective and efficient financial reporting management. With the regional financial accounting system partially significantly and positively influenced by three factors, namely attitude, motivation, and perception. Therefore, policy recommendations should focus not only on improving individual competencies but also on strengthening the system and governance framework synergistically to achieve transparent and reliable public financial reporting. Practical Implications : Findings from 3 international and national journals show that factors influencing the quality of local government financial reports in Indonesia play an important role in strengthening integrated accounting and financial governance systems. Originality/novelty : This research has a strong element of novelty compared to previous research because it combines a systematic literature review (SLR) approach with a very specific focus on the regional financial accounting system during the 2017-2025 period.